Genomic insights into the antimicrobial resistance and virulence of Helicobacter pylori isolates from gastritis patients in Pereira, Colombia - Adalucy Alvarez-Aldana; Odion O. Ikhimiukor; Yina Marcela Guaca-González; Manuela Montoya-Giraldo; Stephanie S. R. Souza; Ana Beatriz Garcez Buiatte; Cheryl P. Andam (BMC Genomics, 2024)
Abstract Background Helicobacter pylori infects the stomach and/or small intestines in more than half of the human population. Infection with H. pylori is the most common cause of chronic gastritis, which can lead to more severe gastroduodenal pathologies such as peptic ulcer, mucosa-associated lymphoid tissue lymphoma, and gastric cancer. H. pylori infection is particularly concerning in Colombia in South America, where > 80% of the population is estimated to be infected with H. pylori and the rate of stomach cancer is one of the highest in the continent. Results We compared the antimicrobial susceptibility profiles and short-read genome sequences of five H. pylori isolates obtained from patients diagnosed with gastritis of varying severity (chronic gastritis, antral erosive gastritis, superficial gastritis) in Pereira, Colombia sampled in 2015. Antimicrobial susceptibility tests revealed the isolates to be resistant to at least one of the five antimicrobials tested: four isolates were resistant to metronidazole, two to clarithromycin, two to levofloxacin, and one to rifampin. All isolates were susceptible to tetracycline and amoxicillin. Comparative genome analyses revealed the presence of genes associated with efflux pump, restriction modification systems, phages and insertion sequences, and virulence genes including the cytotoxin genes cagA and vacA. The five genomes represent three novel sequence types. In the context of the Colombian and global populations, the five H. pylori isolates from Pereira were phylogenetically distant to each other but were closely related to other lineages circulating in the country. Conclusions H. pylori from gastritis of different severity varied in their antimicrobial susceptibility profiles and genome content. This knowledge will be useful in implementing appropriate eradication treatment regimens for specific types of gastritis. Understanding the genetic and phenotypic heterogeneity in H. pylori across the geographical landscape is critical in informing health policies for effective disease prevention and management that is most effective at local and country-wide scales. This is especially important in Colombia and other South American countries that are poorly represented in global genomic surveillance studies of bacterial pathogens.